Psychological Functioning and Living Arrangements among Older Thai People - Sureeporn Punpuing (2022)
In the next two decades, one in three people in Thailand will be older adults aged 60 or over. Industrialization and socioeconomic development have encouraged the migration of young adults from rural to urban areas which has transformed the living arrangements of some older adults. Using culturally sensitive measures, this study investigates the association between living arrangements and psychological functioning net of personal and contextual factors. Data are from a survey of 638 Thai people aged 60 and over conducted in 2012. Results from multiple regression analyses indicate that personal and contextual factors are differentially associated with either psychological wellbeing or depressive symptoms. In contrast, living arrangements are associated with both outcomes. These results suggest that older persons in skipped-generation households (two-generation households consisting of grandparents and grandchildren) are more likely to have lower psychological wellbeing than those who live in multi- and one generational households (with no children living within walking distance), and have higher depressive symptoms than those who live only with their children. Findings indicate that tailored services and policies are needed for older adults in varied living arrangements, particularly those in skipped-generation households.